Persecution of Arab thinkers: (Ali Abdel Razek as an example) - Wadi, Hawraa Kamel; Annad, Ali Jabbar (Al-Adab Journal, 2022)
Since the early days of philosophical thinking, the philosopher tried to change his reality and those around him, so some philosophers faced plights, abuse, injustice, tyranny, and intellectual and physical absence. "Ideas" have no homeland, creed, sect, or address. That is, intellectual and cultural products are not the property of anyone and are not exclusive to anyone, as they belong to all of humanity, so they wanted to save humanity. We tried to focus on some of the personalities who were persecuted in contemporary Arab thought, so we chose, (Ali Abdel Razek).